1995
DOI: 10.1128/jb.177.9.2373-2380.1995
|View full text |Cite
|
Sign up to set email alerts
|

Temperature tolerance of hydrogenase expression in Alcaligenes eutrophus is conferred by a single amino acid exchange in the transcriptional activator HoxA

Abstract: Expression of the soluble (SH) and membrane-bound (MBH) hydrogenases in the facultatively lithoautotrophic bacterium Alcaligenes eutrophus is dependent on the transcriptional activator HoxA and the alternative sigma factor 54 . Deletion analysis revealed that a region 170 bp upstream of the transcriptional start of the SH operon is necessary for high-level promoter activity. Mobility shift assays with DNA fragments containing the SH upstream region and purified ␤-galactosidase-HoxA fusion protein isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
0
32
0
1
Order By: Relevance
“…In A. eutrophus, HoxA binds at the promoter region of the genes encoding the soluble hydrogenase (Zimmer et al, 1995). Expression of the genes encoding the soluble hydrogenase is dependent on RpoN, and purified E. coli IHF protein was also shown to bind at the promoter region (Zimmer et al, 1995). Also, in R. capsulatus, IHF is required for expression of the hydrogenase structural genes (Toussaint et al, 1991;1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In A. eutrophus, HoxA binds at the promoter region of the genes encoding the soluble hydrogenase (Zimmer et al, 1995). Expression of the genes encoding the soluble hydrogenase is dependent on RpoN, and purified E. coli IHF protein was also shown to bind at the promoter region (Zimmer et al, 1995). Also, in R. capsulatus, IHF is required for expression of the hydrogenase structural genes (Toussaint et al, 1991;1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the regulatory cascade that governs hupSL expression in free-living B. japonicum cells resembles hydrogenase regulation in the free-living chemolithotroph Alcaligenes eutrophus and in the photosynthetic bacterium Rhodobacter capsulatus. In A. eutrophus, HoxA binds at the promoter region of the genes encoding the soluble hydrogenase (Zimmer et al, 1995). Expression of the genes encoding the soluble hydrogenase is dependent on RpoN, and purified E. coli IHF protein was also shown to bind at the promoter region (Zimmer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 -independent O 2 consumption was monitored in N 2 -saturated potassium phosphate buffer. ␤-Galactosidase assays were performed as described previously (54), and the activities (in units) were calculated according to the Miller method (33) except that cell density was measured at 436 nm. The level of protein in extracts was determined by the method of Lowry et al (28).…”
Section: Methodsmentioning
confidence: 99%
“…HoxA binds specifically at the upstream regions of the MBH and SH operons and activates transcription in concert with the 54 -containing RNA polymerase (42,54). Transcription activation by HoxA is stimulated by at least two environmental signals: the presence of molecular hydrogen and/or limitation of organic carbon and energy sources (25,42).…”
mentioning
confidence: 99%
“…In A. eutrophus, it has been shown that HoxA, the NtrC-homologous product encoded in the hydrogenase gene cluster, activated the expression of hydrogenase genes under conditions of energy limitation. 16 ) Igarashi et al 17 ) reported that P. hydrogenovora did not fix nitrogen but did reduce nitrate, however, the transcriptional activity of P hup region was not affected by the presence or absence of a nitrogen source (Table). Since the structure of the P. hydrogenovora hydrogenase gene cluster is much more similar to that of A. eutrophus than those of other hydrogenase-containing bacteria, P. hydrogenovora is likely to have a transcriptional regulator operating specifically for an expression of hydrogenase genes.…”
Section: A Search For Cis-acting Elements Upstream Of P Hup Sequencesmentioning
confidence: 99%